Epstein-Barr Virus Episome Physically Interacts with Active Regions of the Host Genome in Lymphoblastoid Cells - Wang, Luopin (J Virol, 2020)
The Epstein-Barr virus (EBV) episome is known to interact with the three-dimensional structure of the human genome in infected cells. However, the exact locations of these interactions and their potential functional consequences remain unclear. Recently, high-resolution chromatin conformation capture (Hi-C) assays in lymphoblastoid cells have become available, enabling us to precisely map the contacts between the EBV episome(s) and the human host genome. Using available Hi-C data at a 10-kb resolution, we have identified 15,000 reproducible contacts between EBV episome(s) and the human genome. These contacts are highly enriched in chromatin regions denoted by typical or super enhancers and active markers, including histone H3K27ac and H3K4me1. Additionally, these contacts are highly enriched at loci bound by host transcription factors that regulate B cell growth (e.g., IKZF1 and RUNX3), factors that enhance cell proliferation (e.g., HDGF), or factors that promote viral replication (e.g., NBS1 and NFIC). EBV contacts show nearly 2-fold enrichment in host regions bound by EBV nuclear antigen 2 (EBNA2) and EBNA3 transcription factors. Circular chromosome conformation capture followed by sequencing (4C-seq) using the EBV origin of plasmid replication (oriP) as a “bait” in lymphoblastoid cells further confirmed contacts with active chromatin regions. Collectively, our analysis supports interactions between EBV episome(s) and active regions of the human genome in lymphoblastoid cells. IMPORTANCE EBV is associated with ∼200,000 cancers each year. In vitro, EBV can transform primary human B lymphocytes into immortalized cell lines. EBV-encoded proteins, along with noncoding RNAs and microRNAs, hijack cellular proteins and pathways to control cell growth. EBV nuclear proteins usurp normal transcriptional programs to activate the expression of key oncogenes, including MYC, to provide a proliferation signal. EBV nuclear antigens also repress CDKN2A to suppress senescence. EBV membrane protein activates NF-κB to provide survival signals. EBV genomes are maintained by EBNA1, which tethers EBV episomes to the host chromosomes during mitosis. However, little is known about where EBV episomes are located in interphase cells. In interphase cells, EBV promoters drive the expression of latency genes, while oriP functions as an enhancer for these promoters. In this study, integrative analyses of published lymphoblastoid cell line (LCL) Hi-C data and our 4C-seq experiments position EBV episomes to host genomes with active epigenetic marks. These contact points were significantly enriched for super enhancers. The close proximity of EBV episomes and the super enhancers that are enriched for transcription cofactors or mediators in lymphoblasts may benefit EBV gene expression, suggesting a novel mechanism of transcriptional activation.